Acute ketone monoester supplementation impairs 20-min time-trial performance in trained cyclists: a randomized, crossover trial - McCarthy, D. G.; Bone, J.; Fong, M.; Pinckaers, P. J.; Bostad, W.; Richards, D. L.; van Loon, L. J.; Gibala, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Acute ketone monoester (KE) supplementation can alter exercise responses, but the performance effect is unclear. The limited and equivocal data to date are likely related to factors including the KE dose, test conditions, and caliber of athletes studied. We tested the hypothesis that mean power output during a 20-min cycling time trial (TT) would be different after KE ingestion compared to a placebo (PL). A sample size of 22 was estimated to provide 80% power to detect an effect size dz of 0.63 at an alpha level of .05 with a two-tailed paired t test. This determination considered 2.0% as the minimal important difference in performance. Twenty-three trained cyclists (N = 23; peak oxygen uptake: 65 ± 12 ml·kg-1 min-1; M ± SD), who were regularly cycling >5 hr/week, completed a familiarization trial followed by two experimental trials. Participants self-selected and replicated their diet and exercise for ~24 hr before each trial. Participants ingested either 0.35 g/kg body mass of (R)-3-hydroxybutyl (R)-3-hydroxybutyrate KE or a flavor-matched PL 30 min before exercise in a randomized, triple-blind, crossover manner. Exercise involved a 15-min warm-up followed by the 20-min TT on a cycle ergometer. The only feedback provided was time elapsed. Preexercise venous [ß-hydroxybutyrate] was higher after KE versus PL (2.0 ± 0.6 vs. 0.2 ± 0.1 mM, p < .0001). Mean TT power output was 2.4% (0.6% to 4.1%; mean [95% confidence interval]) lower after KE versus PL (255 ± 54 vs. 261 ± 54 W, p < .01; dz = 0.60). The mechanistic basis for the impaired TT performance after KE ingestion under the present study conditions remains to be determined.